Highly efficient and reusable polymer supported palladium catalyst for copper free sonogashira reaction in water - Sruthi, Pambingal Rajan; Nimmi, Puthan Purayil; Babu, Sukumaran Santhosh; Anas, Saithalavi (ChemistrySelect, 2022)
Development of a novel, greener and efficient heterogeneous catalytic system for copper free Sonogashira reaction in water is described. This novel catalyst can be easily prepared by a simple method through synthetic modification of nitrile group in Polyacrylonitrile (PAN) using monoethanolamine (MEA) followed by its complexation with palladium chloride (PdCl2). The resulting polymer Pd complex (mPAN-Pd) was characterized by means of Fourier Transform Infrared Spectroscopy (FTIR), Energy-Dispersive X-ray Spectroscopy (EDAX), Inductively Coupled Mass Spectrometry (ICP-MS) and X-ray Photo Electron Spectroscopy (XPS) analyses. mPAN-Pd was then explored as highly efficient heterogeneous catalyst for Sonogashira coupling reaction under copper and ligand free conditions in water affording the corresponding coupling products up to 97 % isolated yield. Moreover, the catalyst was recovered by simple filtration after the reaction and reused for next 5 cycles with excellent stability and activity. This is the first report on the use of ethanolamine modified PAN Pd (II) complex as an efficient heterogeneous catalyst for a coupling reaction.
Keywords: catalysis; green chemistry; Palladium; Polymer Support; Sonogashira coupling